Validation of an improved helical diode array and dose reconstruction software using TG‐244 datasets and stringent dose comparison criteria. (8th November 2016) - Ahmed, Saeed; Nelms, Benjamin; Kozelka, Jakub; Zhang, Geoffrey; Moros, Eduardo; Feygelman, Vladimir
Abstract : The original helical ArcCHECK (AC) diode array and associated software for 3D measurement‐guided dose reconstruction were characterized and validated; however, recent design changes to the AC required that the subject be revisited. The most important AC change starting in 2014 was a significant reduction in the overresponse of diodes to scattered radiation outside of the direct beam, accomplished by reducing the amount of high‐Z materials adjacent to the diodes. This change improved the diode measurement accuracy, but in the process invalidated the dose reconstruction models that were assembled based on measured data acquired with the older version of the AC. A correction mechanism was introduced in the reconstruction software (3DVH) to accommodate this and potential future design changes without requiring updating model parameters. For each permutation of AC serial number and beam model, the user can define in 3DVH a single correction factor which will be used to compensate for the difference in the out‐of‐field response between the new and original AC designs. The exact value can be determined by minimizing the dose‐difference with an ionization chamber or another independent dosimeter. A single value of 1.17, corresponding to the maximum measured out‐of‐field response difference between the new and old AC, provided satisfactory results for all studied energies (6X, 15X, and flattening filter‐free 10XFFF). A library of standard cases recommended by the AAPM TG‐244 Report was used for reconstructed dose verification. The overall difference between reconstructed dose and an ion chamber in a water‐equivalent phantom in the targets was 0.0 %   ±   1.4 % (1 SD). The reconstructed dose on a homogeneous phantom was also compared to a biplanar diode dosimeter ( Delta 4 ) using gamma analysis with 2 %   ( local   dose ‐ error   normalization ) / 2   mm / 10 % cutoff criteria. The mean agreement rate was 96.7 %   ±   3.7 % . For the plans common with the previous comparison, the mean agreement rate was 98.3 %   ±   0.8 %, essentially unchanged. We conclude that the proposed software modification adequately addresses the change in the dosimeter response. PACS number(s): 87.55Qr